Addressing barriers in smart port development: prioritising strategies for effective implementation - Erdogan, Melike; Seker, Sukran; Aydin, Nezir; Ayyildiz, Ertugrul (TAYLOR & FRANCIS LTD, 2025)
The need for efficient and sustainable logistics solutions has been highlighted as the rapid growth of global trade places extraordinary pressure on port systems. The concept of 'smart-ports' has emerged to leverage technologies such as automation, artificial intelligence, the Internet of Things, and big data analytics to enhance port performance as traditional port operations face challenges such as congestion, resource inefficiency, and environmental concerns. However, various political, economic, technological, social, and environmental barriers prevent the successful implementation of smart ports. This study addresses this gap by focusing on the barriers to developing smart ports, using a strategic framework to prioritise solutions. It contributes to the literature by proposing a hybrid decision-making approach that integrates PESTEL, Stepwise Weight Assessment Ratio Analysis (SWARA), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) under fuzzy logic for the first time in the context of smart ports. The study provides a comprehensive roadmap for policymakers and stakeholders to navigate the complexities of smart port implementations successfully. Findings suggest that comprehensive stakeholder engagement for digitalisation, and collaborative governance and regulatory streamlining for smart port development are the most promising strategies.
Keywords: Smart ports; multi-criteria decision-making; SWARA; TOPSIS; PESTEL analysis; Engineering